Detecting land uplift associated with enhanced oil recovery using InSAR in the Karamay oil field, Xinjiang, China. Issue 7 (2nd April 2016) - Ji, Lingyun; Zhang, Yong; Wang, Qingliang; Xin, Yuling; Li, Jin
ABSTRACT: Subsurface fluid injection is a well-established technology that is often used for enhanced oil recovery from oil fields. The injection process can often cause deformation due to changes in pore pressure, which can be measured using interferometric synthetic aperture radar (InSAR). In this study, the Karamay oil field in Xinjiang served as an example and an attempt was made to detect subsurface fluid injection-induced ground surface deformation. First, possible deformation was assessed across the entire Karamay oil field during 2006–2010 by stacking multiple interferometric pairs. Then, the spatiotemporal evolution of deformation around well Hei103 was studied using the small baseline subset (SBAS) algorithm. The results suggest that localized deformation at the Karamay oil field was related to oil production. Additionally, subsurface fluid injection caused obvious surface uplift around the Hei103 well region.